TEKNIK PEMBIBITAN DAN PENANAMAN MANGROVE DI BANYUURIP MANGROVE CENTER, DESA BANYUURIP, KECAMATAN UJUNGPANGKAH, KABUPATEN GRESIK - Defri Yona; Nurin Hidayati; Syarifah Hikmah Julinda Sari; Irfan Naufal Amar; Kharisma Wisnu Sesanty (Politeknik Negeri Jember, 2018)
Banyuurip is one village in East Java that has successfully replanting its mangrove forest. Mangrove forest in Banyuurip had experienced losses due to changes into aquaculture and also abrasion from the Java Sea. However, with the concern and willingness of local fishermen who realized the loss of mangrove brought significant impact to their fish catching, mangrove replanting was carried out since 2007. This effort went well because they did the seedling process by themselves. Seedling process in Banyuurip is dominated by mangrove Avicennia sp and Rhizophora because these mangroves are found in high numbers in Banyuurip. Seedling is carried out using polybag and the germination was conducted in an area called ‘bedengan’ to protect the seeds from the sun. The seeds are watered using water pump regularly and supervision is conducted to prevent the seeds from being eaten by crab. At present, mangrove seedling in Banyuurip is running well and the seeds are either used by themselves or are selling to another mangrove places.